Involvement of the C-terminal residues of the 20,000-dalton light chain of myosin on the regulation of smooth muscle actomyosin. - Ikebe, M (1994)
The segment of smooth muscle regulatory light chain essential for the phosphorylation dependent activation of actomyosin motor activity and the binding of myosin heavy chain was identified. The C-terminal domain of the 20-kDa light chain, which is less conserved than the rest of the polypeptide among various muscle types, was mutated by either deletion or substitution of amino acid residues and the mutant light chains were then incorporated into myosin by subunit exchange. Deletion of Lys149-Ala166 markedly reduced the affinity of the light chain for the heavy chain, whereas the C-terminal five residues, Lys167-Asp171, did not contribute to the binding affinity. Deletion of Lys149-Phe158 abolished the phosphorylation-dependent activation of actomyosin ATPase activity as well as superprecipitation activity. These results suggest that the C-terminal domain of the regulatory light chain is critical for transmitting the change in the conformation of the regulatory light chain induced by phosphorylation at Ser19 to the heavy chain.